Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Merger Dan Akuisisi (Studi Pada Perusahaan Yang Melakukan Merger dan Akuisisi tahun 2013 di Bursa Efek Indonesia) - Enny Tiya Rosyandy (e_Jurnal Ilmiah Riset Akuntansi, 2017)
AbstractThis study aims to assess the difference between the performance of your company before andafter mergers and acquisitions. Sample in this research is a number of 15 companies withresearch results show that the financial performance is assessed from net profit margin,return on asset, return on equity, current ratio, and debt to asset show that return on equityhas differences before mergers and acquisitions and after Mergers and acquisitions whereasother variables have no difference between before and after mergers and acquisitions.Keywords: financial performance, net profit margin, return on asset, return on equity,current ratio, debt to asset ratio